ANGIOPOIETIN-LIKE GROWTH FACTOR CONTROLS APPETITE VIA LEPTIN SIGNALING - Heo, Jun Young; Jang, Yunseon; Kim, Soo Jeong; Lee, Min Joung; Ryu, Min Jeong; Park, Jong Il; Kweon, Gi Ryang (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Hypothalamic regulation of appetite governs whole-body energy balance. Satiety is regulated by endocrine factors, including leptin, and impaired leptin induction causes obesity. Angiopoietin-like growth factor (AGF) promotes energy expenditure in the periphery, and systemic reconstitution of AGF antagonizes obesity. However, whether hypothalamic AGF plays a role in controlling food intake remains unknown. METHODOLOGY Immunofluorescence staining was used to identify the intensity of AGF and leptin signaling in the hypothalamus. In addition, to verify the function of AGF in the hypothalamus, we used stereotaxic intracerebroventricular injection with recombinant AGF. RESULTS We demonstrated that AGF is expressed in proopiomelanocortin (POMC)-positive neurons located in the arcuate nucleus (ARC) of the hypothalamus. AGF expression was stimulated by leptin-induced STAT3 phosphorylation. Notably, intracerebroventricular injection of AGF significantly reduced food intake by stimulating phosphorylation of CREB in the POMC and increasing α-melanocyte-stimulating hormone (α-MSH) content in the hypothalamus. We also found that hypothalamic injection of AGF significantly suppressed food intake and decreased body weight in high-fat-diet–induced obese mice, which exhibit leptin insensitivity. CONCLUSION Collectively, our findings demonstrate that hypothalamic AGF provokes the anorectic melanocortin pathway and mediates leptin signaling to prevent obesity.